2003
DOI: 10.1046/j.1440-169x.2003.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 17‐α‐ethynylestradiol on germ cell proliferation in organ and primary culture of medaka (Oryzias latipes) testis

Abstract: Organ cultures and primary cell cultures of medaka ( Oryzias latipes ) testis were compared with respect to cell viability and cell proliferation. The analysis by fluorescence microscopy and flow cytometry showed that in both cultures the cells remained viable for at least 1 day and cell proliferation could be analyzed reliably by BrdU incorporation. The proliferating cells were mostly spermatogonia located at the periphery of the testis in tissue sections. Both culture systems were used to study the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…Our results on oestrogen-mediated reduction of germ cell proliferation are in accordance with previous observations in fish and amphibian species (Song & Gutzeit 2003, Tsai et al 2005, Chaves-Pozo et al 2007, although these studies did not determine the changes in germ cell masses (i.e. provided data on relative changes in the germ cell compartment), and did not always identify the specific stage of spermatogenesis affected.…”
Section: Discussionsupporting
confidence: 92%
“…Our results on oestrogen-mediated reduction of germ cell proliferation are in accordance with previous observations in fish and amphibian species (Song & Gutzeit 2003, Tsai et al 2005, Chaves-Pozo et al 2007, although these studies did not determine the changes in germ cell masses (i.e. provided data on relative changes in the germ cell compartment), and did not always identify the specific stage of spermatogenesis affected.…”
Section: Discussionsupporting
confidence: 92%
“…The labelled cells had a relatively large diameter which is characteristic of spermatogonia and newly formed primary spermatocytes. In keeping with this finding is the observation that in BrdU-treated whole testis the labelled cells are located in the periphery of the organ (Song and Gutzeit 2003). We obtained no evidence that somatic cells contribute significantly to the BrdU incorporation quantified in the described assays.…”
Section: Discussionsupporting
confidence: 79%
“…3b). More than 80% of the BrdU-labelled cells had a Based on their size the labelled cells are likely to be spermatogonia and primary spermatocytes, a conclusion that is corroborated by histological data of BrdU-labelled testes (Song and Gutzeit 2003).…”
Section: Cell Proliferationmentioning
confidence: 60%
“…Gametogenesis is largely under the control of steroid hormones in vertebrates (Song and Gutzeit, 2003), whereby xenobiotics may interfere with hormone action and consequent impacts. Although it is suggested that the molecular and cellular effects of hormonally active compounds are best studied under well-defined conditions in vitro (Song and Gutzeit, 2003), observations from sperm cell maturity levels and sperm cell counts indicated that the animals at the experimental sites were less sexually advanced than those at the reference site.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is suggested that the molecular and cellular effects of hormonally active compounds are best studied under well-defined conditions in vitro (Song and Gutzeit, 2003), observations from sperm cell maturity levels and sperm cell counts indicated that the animals at the experimental sites were less sexually advanced than those at the reference site. Sperm count is a very common biomarker of testis function in humans, and the use of flow cytometry in fertility assays has been helpful, and it allows for other analysis such as DNA content and integrity (Eustache and others, 2001).…”
Section: Discussionmentioning
confidence: 99%